Edukasi Pertumbuhan dan Perkembangan pada Batita - Fatmawati, Nurul; Zulfiana, Yesvi; Handayani, Sri; Soekmawaty Riezqy Ariendha, Dian; Setyawati, Irni (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Child growth and development in Indonesia still needs serious attention; the rate of delayed growth and development is still quite high, with around 5-10% experiencing general developmental delays. The child population in Indonesia is about 33% of the total population, which is around 83 million, and every year, the number of child population will increase. This service aims to increase mothers' knowledge about the growth and development of children aged 1 to 3 years. The method in this service is Participatory Learning Action (PLA). The results of this service showed an increase in mothers' knowledge about the growth and development of toddlers from 14.6% to 93% after receiving education. This service concludes that mothers with children aged 1 to 3 years are expected to always monitor children's growth and development as one of the detections of growth and development abnormalities.